PENGUKURAN DAN ANALISIS KINERJA INDUSTRI KREATIF KERAJINAN BATIK XYZ WUKIRSARI BANTUL - Yasrin Zabidi; Marni Astuti (Jurnal Ilmiah Dinamika Teknik, 2020)
The problem in XYZ Wukirsari's batik handicraft creative industry is that performance measurement has not been done, even though performance is an important factor affecting the company's progress and setbacks. Researchers carry out performance measurement and analysis with the aim of knowing the criteria and performance indicators, knowing the value of the performance of each performance indicator and total performance, knowing the actual performance achievement of initial performance, and achieving actual performance against target performance. The research method uses a balanced scorecard to determine performance criteria and indicators and omax to measure performance. The results obtained by 4 criteria (financial,consumer,internal business processes,learning andgrowing). There are 6 performance indicators (IK) formed. IK1 score is good (8 score), IK2 is good (score 6), IK3 is very good (score 10), IK4 is very good (score 10), IK5 is good (score 6), and IK6 is good (score 6). Overall performance value was 7.66 with a performance score of 8 (good). Achievement of actual performance to the initial performance of each performance indicator and overall has exceeded the initial performance. Partially IK3 and IK4 have reached the target, while IK1, IK2, IK5 and IK6 have still not reached the target. Overall total actual performance when compared with total target performance has not yet reached the target set. Keywords: Performance, Measurement, Batik